Prolonged QT interval in ST-elevation myocardial infarction: predictors and prognostic value in medium-term follow-up. Issue 6 (June 2016) - Galluzzo, Alessandro; Gallo, Cristina; Battaglia, Alberto; Frea, Simone; Canavosio, Federico G.; Botta, Michela; Bergerone, Serena; Gaita, Fiorenzo
Abstract : Aims: The prognostic role of corrected QT interval in ST-elevation myocardial infarction is still unknown. This study aims to identify the prognostic value of corrected QT interval prolongation (≥480 ms) in acute coronary syndrome. Methods: One hundred and eighty-five consecutive patients with ST-elevation myocardial infarction were prospectively enrolled and electrocardiographic monitoring of corrected QT interval was performed during the hospitalization. Results: Over a mean period of 17.6 ± 11 months, 16 (8.6%) patients died because of cardiovascular diseases, 6 (3.2%) patients experienced aborted sudden cardiac death, 3 (1.6%) cerebral ischemic strokes, 11 (6%) recurrent myocardial ischemia and 6 (3.2%) acute heart failure. At univariate analysis a corrected QT interval peak of at least 480 ms relates to cardiovascular death ( P  < 0.001), aborted sudden cardiac death ( P  = 0.037), cerebral ischemic stroke ( P  = 0.016) and recurrences of myocardial infarction ( P  = 0.032). Multivariate analysis confirms its role an independent predictor of cardiovascular death [odds ratio 6.38, 95% confidence interval (CI) 1.77–22.92, P  = 0.004], together with an ejection fraction of 35% or less (odds ratio 4.20, 95% CI 1.24–14.16, P  = 0.021). The presence of either corrected QT of at least 480 ms or ejection fraction of 35% or less increases the sensitivity and the accuracy to correctly predict cardiovascular death without a significant reduction in specificity (sensitivity 88%, specificity 69%, accuracy 88%, area under curve 0.83, 95% CI 0.72–0.94, P  < 0.01). Conclusion: A corrected QT interval peak of at least 480 ms in the acute phase of ST-elevation myocardial infarction is an independent predictor of cardiovascular death. Its association with reduced ejection fraction (⩽35%) increases risk stratification accuracy.